Molecular Determinants of in vitro Plant Regeneration: Prospects for Enhanced Manipulation of Lettuce (Lactuca sativa L.) - Bull, Tawni; Michelmore, Richard (Frontiers in Plant Science, 2022)
In vitro plant regeneration involves dedifferentiation and molecular reprogramming of cells in order to regenerate whole organs. Plant regeneration can occur via two pathways, de novo organogenesis and somatic embryogenesis. Both pathways involve intricate molecular mechanisms and crosstalk between auxin and cytokinin signaling. Molecular determinants of both pathways have been studied in detail in model species, but little is known about the molecular mechanisms controlling de novo shoot organogenesis in lettuce. This review provides a synopsis of our current knowledge on molecular determinants of de novo organogenesis and somatic embryogenesis with an emphasis on the former as well as provides insights into applying this information for enhanced in vitro regeneration in non-model species such as lettuce (Lactuca sativa L.).